Strategic analysis - Kofola ČeskoSlovensko a.s. on Czech Market - Abionyan, Grigory (2020)
The topic of my bachelor thesis is to perform a strategic analysis of Kofola ČeskoSlovensko a.s. The purpose of this bachelor thesis is to analyze both external and internal environments using appropriate strategic analysis methods. It will be started with a theoretical part, where I will describe tools, which will be used to perform a strategic analysis in the practical part of the thesis. And subsequently, I will suggest opportunities for the future, so the company retains its valuable competitive position.